A Review of the DAC Evaluation Criteria: Upgrading Efficiency - Joaquin de la Concha (The Evaluation Center at Western Michigan University, 2020)
Background: Efficiency has remained for long time the Cinderella of evaluation practice. According to several meta-evaluations only a small number of evaluations include robust and meaningful assessments in this field. Purpose: Following the review of the Development Assistance Committee's (DAC) evaluation criteria this article reviews the main causes of efficiency remaining in a secondary role in evaluation practices and proposes: 1) upgrading it through broadening the current economic definition of efficiency, and 2) proposing a set of four evaluation dimensions revolving around the principle of sound financial management, social perceived value, result-based budgeting and interconnectedness with other criteria. Setting: Not applicable. Intervention: Not applicable. Research design: Literature review and empirical pilot testing of proposed evaluation methodology. Data collection & analysis: Qualitative analysis. Findings: This paper calls for a shift in focus from efficiency to a broader enriched principle of sound financial management including a strong partner-based focus and highlighting management as a pre- condition "sine qua non" for an intervention to be efficient. Efficiency assessments would then be twofold: managerial (procedures, policies and practices that lay out the requirements for efficiency to take place) and substantial (context, circumstances and reasoning for the existing budget balance between results and target groups). The key aspects of the proposal involve four proposed dimensions to be analysed under this renewed criteria that imply audits and evaluations come much closer and look at each other. Keywords: DAC evaluation criteria; efficiency; economy; equity; sound financial management; performance audit.